A 10-color flow cytometry panel for diagnosis and minimal residual disease in chronic lymphocytic leukemia. Issue 10 (24th August 2021) - Bazinet, Alexandre; Rys, Ryan N.; Barry, Amadou; Greenwood, Celia M. T.; Young, Yoon Kow; Mendoza, Alma; LaPorta, Ida; Wever, Claudia M.; Mercier, François E.; Johnson, Nathalie A.
Abstract: Diagnosis and minimal residual disease (MRD) monitoring of chronic lymphocytic leukemia (CLL) by flow cytometry currently requires multiple antibody panels. We added CD23 and CD200 to the EuroFlow TM lymphoid screening tube (LST) to create a 10-color modified LST (mLST) capable of diagnosing typical CLL in a single tube. We then explored if the mLST could be used for MRD by comparing its performance to the European Research Initiative on CLL (ERIC) panel using spiked cryopreserved and fresh patient samples. Over 1 year of use in our clinical laboratory, the mLST diagnosed CLL without further immunophenotyping in 56% of samples with an abnormal clone. There was good agreement in MRD results between the mLST and ERIC panels. Therefore, the mLST can streamline CLL diagnosis by reducing technician time and the number of panels required. It may have the potential to screen for MRD in laboratories without access to dedicated panels (ERIC).